2010
DOI: 10.1517/14740338.2010.497138
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of higher doses of deferasirox: better efficacy but not effective iron removal from the heart and increased risks of serious toxicities

Abstract: Only few patients may benefit from the introduction of higher doses of deferasirox. There is a need for introducing more effective prophylactic measures. Safer, more effective and less costly chelation treatments are available using deferiprone, deferoxamine and their combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…14 In addition, safety of DFX is reported in patients with CKD undergoing hemodialysis 30 and myelodysplastic syndrome; 31 however, it is noteworthy that side effect of DFX is mild and reversible increases in serum creatinine levels. 31,32 Fanconi syndrome is also reported as a rare complication (complication rate is 0.1-1%) in both adult and pediatric patients treated with DFX. 33 In other words, the effects of DFX on renal function remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, safety of DFX is reported in patients with CKD undergoing hemodialysis 30 and myelodysplastic syndrome; 31 however, it is noteworthy that side effect of DFX is mild and reversible increases in serum creatinine levels. 31,32 Fanconi syndrome is also reported as a rare complication (complication rate is 0.1-1%) in both adult and pediatric patients treated with DFX. 33 In other words, the effects of DFX on renal function remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…43 Moreover, increasing the dose of the drug is problematic as evidence of toxicity has also increased. 47 The efficacy of DFX might also be increased by splitting the dose. Chang et al reported that serum ferritin levels declined by nearly 40% in 11 patients, who were unresponsive to once daily doses of DFX, after treatment for 6 months with twice daily dosing, the total dosage being the same.…”
mentioning
confidence: 99%
“…Total 37 patients (23 males, 14 females), ages 3 weeks to 34 years (mean age 15, standard deviation 7), were included. Underlying pathologies for the subjects were beta thalassemia ( 13), leukemia/lymphoma (6), Diamond–Blackfan anemia (4), aplastic anemia (4), sickle cell anemia (3), red cell aplasia (2), and one case each of hemophagocytic syndrome, pyruvate kinase deficiency associated anemia, Ewing sarcoma, neonatal hemochromatosis, and Fanconi anemia. All studies were performed in a Health Insurance Portability and Accountability Act (HIPPA) ‐compliant fashion on a GE 1.5T HDx scanner (GE Healthcare, Waukesha, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Without accurate assessment of degree of iron overload in each organ, including the liver, clinicians may increase doses of chelation when this is not truly indicated ( 1, 2). These higher doses may also lead to increased toxicity (3). Thus, accurate quantification of iron deposition in various organs is essential for therapeutic decision‐making.…”
mentioning
confidence: 99%
See 1 more Smart Citation